2007
DOI: 10.1126/science.1138438
|View full text |Cite
|
Sign up to set email alerts
|

The Calyptogena magnifica Chemoautotrophic Symbiont Genome

Abstract: Chemoautotrophic endosymbionts are the metabolic cornerstone of hydrothermal vent communities, providing invertebrate hosts with nearly all of their nutrition. The Calyptogena magnifica (Bivalvia: Vesicomyidae) symbiont, Candidatus Ruthia magnifica , is the first intracellular sulfur-oxidizing endosymbiont to have its genome sequenced, revealing a suite of metabolic capabilities. The genome encodes major chemoautotrophic pathways as well as pathways for biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
228
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(239 citation statements)
references
References 22 publications
9
228
0
2
Order By: Relevance
“…SUP05 is abundant in oxic/anoxic interfacial environments such as deep-sea hydrothermal plumes (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010), oxygen minimum zones (Stevens and Ulloa, 2008;Lavik et al, 2009;Walsh et al, 2009;Canfield et al, 2010) and symbioses with deep-sea bivalves (Newton et al, 2007). Our data set supports previous genomic studies that showed that members of this group are chemolithoautotrophic, obtaining energy by coupling sulfur oxidation to reduction of nitrate and/or oxygen (Newton et al, 2007;Walsh et al, 2009). The increased abundance of SUP05 sox gene transcripts in the Guaymas Basin plume-among the most plume-enriched genes in the metatranscriptome-provides evidence that SUP05 responds to reduced sulfur compounds commonly found within the plume environment (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…SUP05 is abundant in oxic/anoxic interfacial environments such as deep-sea hydrothermal plumes (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010), oxygen minimum zones (Stevens and Ulloa, 2008;Lavik et al, 2009;Walsh et al, 2009;Canfield et al, 2010) and symbioses with deep-sea bivalves (Newton et al, 2007). Our data set supports previous genomic studies that showed that members of this group are chemolithoautotrophic, obtaining energy by coupling sulfur oxidation to reduction of nitrate and/or oxygen (Newton et al, 2007;Walsh et al, 2009). The increased abundance of SUP05 sox gene transcripts in the Guaymas Basin plume-among the most plume-enriched genes in the metatranscriptome-provides evidence that SUP05 responds to reduced sulfur compounds commonly found within the plume environment (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Peptide sequence from SUP05-derived Dsr proteins were used as query in similarity searches against the NCBI nr-protein database. The only sequences that were 100% identical to the peptides were from the SUP05-related sulfur-oxidizing symbionts of deep-sea clams and mussels (Kuwahara et al, 2007;Newton et al, 2007) and Dsr sequences recovered from an oxygen minimum zone . Five of the six peptides from SUP05-related SoxA and SoxB were also specific to SUP05 proteins.…”
Section: Metabolism Of the Sup05 Cladementioning
confidence: 99%
“…The Osedax symbionts possess many genes devoted to the specific degradation of branched-chain amino acids, which also results in the generation of propionyl-CoA, rather than acetyl-CoA (Muñ oz-ElĂ­as et al, 2006), thus increasing the necessity for the methylcitrate cycle. The observation of genes for these two TCA shunts in both Osedax symbionts, as well as in the marine bivalve symbiont, Ruthia magnifica (Newton et al, 2007), suggests that they, too, may be important for intracellular life. Again, however, a more thorough comparison between heterotrophic symbionts and pathogens is critical to our understanding of the relative importance of these pathways for symbiosis.…”
Section: Genomic Implications For Intracellular Lifementioning
confidence: 99%
“…New details have emerged regarding the range of adaptations used by endosymbionts, parallels with pathogens, provisioning from symbiont to host and many ecological aspects, including transmission between host generations and the duality of negotiating between host-associated and free-living lifestages. Recent advances in molecular biology and genomics have enabled this insight for chemosynthetic symbionts, in particular, hosted by the marine oligochaete Olavius algarvensis (Woyke et al, 2006), vesicomyid clam species (Kuwahara et al, 2007;Newton et al, 2007), the siboglinid tubeworm Riftia pachyptila (Robidart et al, 2008) and the heterotrophic symbionts of wood-boring bivalves (Yang et al, 2009). …”
Section: Introductionmentioning
confidence: 99%